Pengunaan Big Data dan Dampaknya di Dalam Dunia Politik: Munculnya Sikap Hopeful Ignorance Dalam Ragam Relasi Antarmanusia - Cicilia Damayanti (Litbang STFT Widya Sasana Malang, 2023)
The advent of digital technology has brought significant changes to political life, particularly in the use of big data for election campaigns. However, the use of psychographics in data analysis raises concerns about the manipulation of human behaviour and the potential harm it may cause. This article aims to explore the impact of psychographics on society in the digital era and the need for multiculturalism in computer programming. This study aims to examine the use of psychographics in political campaigns and its impact on society. Additionally, the study aims to highlight the need for multiculturalism in computer programming and the importance of data protection. The research method used in this study is book analysis, focusing on politics, technology, and big data. The study analyses the case of Cambridge Analytica and how it used psychographics to manipulate human behaviour. The study shows that the use of psychographics can lead to the creation of paradigms that promote hopeful ignorance, leading to a homogeneous society that may be vulnerable to societal explosions. Furthermore, the study highlights the importance of multiculturalism in computer programming to avoid bias and the need for data protection through cryptography. The study concludes that the use of psychographics in data analysis must be critically examined to avoid manipulation and harm to society. Furthermore, computer programs must embrace multiculturalism to avoid bias, and data protection must be prioritized to maintain privacy and security. Additionally, political candidates should be investigated thoroughly to reveal their authenticity beyond their ethos.